Data reasoning to shape tree patches: optimising climate change adaptation in urban canyons - Francesca Mosca; Gabriele Oneto; Martina Guasco; Katia Perini (Techne, 2025)
This paper aims to define a methodological framework and an operational approach for optimising the location, shape, and size of trees (or other NbS) within the surrounding urban morphology to locally reduce the urban heat island (UHI) effect and identify correlations between urban configurations and NbS performance. The goal is to overcome current limitations, which include the lack of a systematic approach to maximising NbS performance in locally mitigating UHI. Based on the model of the urban canyon, the proposed theoretical and computational approach includes the definition of key performance indicators and their calculation to implement a multi-objective optimisation.